Tailoring biologic therapy for real-world rheumatoid arthritis patients. (4th May 2021) - Romano, Ciro; Esposito, Sergio; Ferrara, Roberta; Cuomo, Giovanna
ABSTRACT: Introduction : The cornerstone of rheumatoid arthritis (RA) therapy relies on the treat-to-target strategy, which aims at dampening inflammation as soon as possible in order to achieve persistent low disease activity or, ideally, remission, according to validated disease activity measures. Traditional disease-modifying antirheumatic drugs (DMARDs) may be chosen in monotherapy or in combination as first-line therapy; in case of an unsatisfactory response after a 3-6-month trial, biologic therapy may be commenced. Areas covered : Real-life RA patients may present with concomitant comorbidities/complications or be in peculiar physiological states which raise more than one question as to which biotherapy may be more well suited considering the whole clinical picture. Therefore, a thorough literature search was performed to identify the most appropriate biologic therapy in each setting considered in this review. Expert opinion : Here we provide suggestions for the use of biologic drugs having a predictable better outcome in specific real-world conditions, so as to ideally profile the patient to the best of the current knowledge.